Influence of Xanthomonas euvesicatoria on quality parameters of pepper seed from Serbia - Živković, Ivana; Iličić, Renata; Barać, Goran; Damnjanović, Jelena; Cvikić, Dejan; Trkulja, Nenad; Popović Milovanović, Tatjana (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2023)
The present study focused on detecting bacteria of the Xanthomonas spp. complex (X. euvesicatoria, X. vesicatoria, X. perforans and X. gardneri) and examining their influence on certain quality parameters of pepper seed collected from the territory of Smederevska Palanka (Serbia). The analysis included 27 non-commercial pepper seed genotypes (including chili and sweet pepper) collected in 2021. Several parameters of the quality of analyzed pepper seed (germination energy, total germination, moisture and seed health) were determined. The results showed that out of a total of 27 analyzed samples of pepper seed, the presence of X. euvesicatoria was detected in 13 of them. The presence of X. vesicatoria, X. gardneri and X. perforans was not confirmed. Germination energy of infected seed was 52-84%, and of bacteria-free seed 63-90%; total germination of infected seed was 66-91%, and of bacteria-free seed 80-95%. Seed moisture of infected seed samples was 6.1-12%, and of bacteria-free seed 6.2-8.1%. These parameters did not show significant statistical difference (p>0.05). The presence of seed-borne fungi Fusarium sp. accounted for up to 3% in 25 samples, while it was up to 6% in the remaining two; Alternaria sp. ranked from 1-4% in 25 samples, and up to 5% in only two samples. The results led to a conclusion that the bacterium X. euvesicatoria is the predominant pathogen of the Xanthomonas spp. complex, but it did not affect the quality parameters of the tested pepper seed.